Anesthesia Management in Aneurysm Clipping Surgery with Chilaiditi Syndrome: Case Report - Putu Pramana Suarjaya; Wisnu Wardhana (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Chilaiditi syndrome is a radiological finding characterized by the interposition of a segment of the colon or small intestine between the liver and the diaphragm, which may be associated with gastrointestinal symptoms. Most patients with a Chilaiditi radiographic appearance remain asymptomatic and retain the condition throughout life; in such asymptomatic cases, it is referred to as the Chilaiditi sign. In this case, a 79-year-old female patient presented with subarachnoid hemorrhage (SAH) due to a ruptured posterior communicating artery (PCom) aneurysm, requiring aneurysm clipping under general anesthesia. During the preoperative evaluation, the Chilaiditi sign was identified on chest x-ray. Perioperative preparation, including both preoperative and postoperative management, played a crucial role in stabilizing the patient’s condition. The selection of appropriate anesthetic drugs and techniques based on clinical indications was essential. The patient received omeprazole to prevent complications such as aspiration or Mendelson’s syndrome. Induction was performed using thiopental, remifentanil, and rocuronium, aiming for a rapid onset of action to facilitate intubation without the use of rapid sequence intubation (RSI). This anesthetic regimen, combined with the surgical technique, yielded favorable outcomes. No postoperative anesthetic or surgical complications were observed, such as aspiration pneumonia, desaturation, or signs of increased intracranial pressure. These findings suggest that general anesthesia without RSI, utilizing a combination of thiopental, remifentanil, and rocuronium, can be safely and effectively employed in patients undergoing intracranial aneurysm clipping procedures, even in the presence of comorbid Chilaiditi syndrome.